P37 Changes in daily physical activity in COPD. (14th November 2013) - Albarrati, AM; Gale, NS; Enright, S; Munnery, IC; Munnery, MM; Cockcroft, JR; Shale, DJ
Abstract : Background: COPD is associated with extrapulmonary manifestations that worsen patient's daily physical activity (DPA)(1). However, changes in DPA over time and contributing factors in this population have not been established. We hypothesise that patients with COPD would have lower DPA after one year. Method: As part of a longitudinal study in COPD (ARCADE), DPA was recorded as the number of steps using a multisensor armband (SenseWear Pro armband) in 28 patients with stable COPD for 7 days and repeated after one year for a further 7 days. Spirometry, body composition, handgrip strength (HGS), six-minute walk distance (6MWD), the COPD assessment test (CAT) were also recorded. Results: Patients mean (SD) age was 69 (7) years, BMI 27.2 (4.7) Kg/m 2 and FEV1 % predicted 52 (15). After one year, there was a reduction in the number of daily steps by 498 (218) steps and fat free mass (FFM) 1.10 (1.75) kg, with an increase in fat mass (FM) 1.06 (2.24) kg and FFM/FM 0.11 (01), all p < 0.01. No changes were observed in FEV1 %, BMI, HGSor 6MWD. The rate of decline in the number of steps was 12.3% per year which related to baseline FFM, r = -0.51 and HGS, r = -0.53, all p < 0.01. Linear regression analysis showed that FFM and HGS can predict 23% and 26% respectively of the variability in the reduction in the number of steps. Conclusion: There was a significant reduction in daily physical activity after one year, which related to baseline FFM and HGS, but was not associated with lung function and 6MWD. Despite maintaining the BMI level, there was a fat free mass turnover, which may indicate a hidden muscle catabolism. Therefore, early management to prevent muscle mass loss would improve patient's daily physical activity and quality of health. References: Watz, K et al (2008) AJRCCM 177(7), pp.743–751.